2022
DOI: 10.1038/s41467-022-31414-0
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in DNA polymerase δ subunit 1 co-segregate with CMD2-type resistance to Cassava Mosaic Geminiviruses

Abstract: Cassava mosaic disease (CMD) suppresses cassava yields across the tropics. The dominant CMD2 locus confers resistance to cassava mosaic geminiviruses. It has been reported that CMD2-type landraces lose resistance after regeneration through de novo morphogenesis. As full genome bisulfite sequencing failed to uncover an epigenetic mechanism for this loss of resistance, whole genome sequencing and genetic variant analysis was performed and the CMD2 locus was fine-mapped to a 190 kilobase interval. Collectively, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Phenotypic variation and broad-sense heritability for CMD, DMC and TCC All the three traits phenotyped had considerable variation, with CMDs showing typical bimodal distribution that had clearcut separation between symptomless plants and those with varying severity levels (Figure 1). The white-fleshed population evaluated for CMD had 73.4% of the genotypes scoring 1 or 2 for CMD severity and were subsequently categorized as resistant (Lim et al, 2022), while the remaining genotypes were susceptible, with CMDs varying between 3 and 5. The mean CMDs score in the population was 1.67.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenotypic variation and broad-sense heritability for CMD, DMC and TCC All the three traits phenotyped had considerable variation, with CMDs showing typical bimodal distribution that had clearcut separation between symptomless plants and those with varying severity levels (Figure 1). The white-fleshed population evaluated for CMD had 73.4% of the genotypes scoring 1 or 2 for CMD severity and were subsequently categorized as resistant (Lim et al, 2022), while the remaining genotypes were susceptible, with CMDs varying between 3 and 5. The mean CMDs score in the population was 1.67.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the large proportion of variation in CMDs unexplained by the marker effects indicates the need for continuous improvement for effective operationalization of MAS platforms in cassava. Through whole genome sequencing and genetic variant analysis, ( Lim et al., 2022 ) fine-mapped the CMD2 locus to a 190 kilobase and identified additional nonsynonymous SNP in DNA polymerase δ subunit 1 (MePOLD1) as the functional gene on chromosome 12 responsible for CMD2 resistance. That study generated eight novel KASP markers that, when incorporate into the existing genomic resource, could reinforce prospects of MAS for CMD2 resistance in cassava breeding.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its monogenetic nature and its wide use in modern varieties, the resistance provided is robust; during more than 20 years of its use, resistance breaking has never been observed. Recent evidence suggests that the outstanding characteristics of CMD2 resistance in cassava are associated with mutations in the DNA polymerase δ subunit 1 (MePOLD1) located within the CMD2 locus on chromosome 12 ( Lim et al., 2022 ).…”
Section: Viruses Infecting Cassava In Africamentioning
confidence: 99%
“…However, most of the other detected DMRs were hypoDMRs (i. e. regions showing decreased methylation in the DMS3-ZF lines) rather than hyperDMRs (increased methylation in the DMS3-ZF lines). An overall decrease in genome methylation has been attributed to the plant tissue culture process in cassava 31 and in many other plant species including maize 32 , rice 33 and oil palm 34 . Cross referencing the observed DMRs with the 1,542 potential off-targets revealed that very few of DMRs (particularly hyperDMRs) fell into off-target regions, and the chance was indistinguishable from the random control regions (Supplementary Fig.…”
Section: Establishing Methylation At the Mesweet10a Promotermentioning
confidence: 99%